VOLATILE COMPOUND ANALYSIS OF AROMATIC RICE MUTANT LINES USING HS-SPME/GC-MS - Riadi, Muh (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Volatile compound is one of the key factors for aromatic components of rice. This study aimed to identify the key aroma components and their relationship with plant productivity in the Pare Bau variety mutant lines and its wild type. Volatile extraction was carried out using the headspace solid-phase microextraction (HS-SPME) method and analysed by the Gas Chromatography-Mass Spectroscopy (GC-MS) instrument. The results of the identification of volatile compounds showed a total of 224 compounds in the mutant lines and wild type. However, only 14 compounds were suspected as key aroma compounds in Pare Bau rice, namely 2-Acetyl-1-pyrroline, Indole, 1-Octanol, 1-Octen-3-ol, 2,4-Nonadienal, (E,E)-, Octanal, 2-Nonenal, (E)-, 2-Octenal, (E)-, Decanal, Hexanal, Nonanal, Furan, 2-pentyl-, toluene and vanillin. The results on aroma compounds of mutant lines using principal component analysis showed that there were differences in the main characteristics of several strains and wild type. There was no relationship between increasing volatile concentration and plant productivity, vice versa.